Dattaka-tilakaḥ: the Sanskrit text critically edited with the editor'sṬīkā named Dīpti along with English and Bengali translations together with an elaborate introduction and appendices - Bhavadeva; Shastri, Jaydeb Ganguly. (The Asiatic Society, 2004)
Sanskrit text with Tilakadīpti Sanskrit commentary and translations on adoption according to Hindu law.
Sanskrit text with Tilakadīpti Sanskrit commentary and translations on adoption according to Hindu law.
English, Bengali, and Sanskrit(Sanskrit in roman and Devanagari).
Keywords: Domestic relations (Hindu law) / http://id.loc.gov/authorities/subjects/sh85038938